Trichomes morphology and density analysis in some "Nepeta" species of Iran - Mehdi Talebi, Seyed; Ghorbani Nohooji, Majid; Yarmohammadi, Mahboobeh; Azizi, Narjes; Matsyura, Alex (Mediterranean Botany, 2018)
Nepeta are widely distributed worldwide and in different parts of Iran where seventy-nine species were registered. The essential oil of these aromatic plants, which accumulates and secrets by trichomes, has been used in medicinal and industrial products. In addition, these epidermal structures can be used as taxonomic traits. We examined the morphology and density of leaves trichomes of twelve Nepeta species using the light and scanning electron microscopes. Three types of indumentum are found in these species, which composed of two main types of glandular: peltate and capitate, and nonglandular; branched and unbranched trichomes. The number of the observed hairs differed between the studied species and analyses of variant test (ANOVA) showed significant variations among some of them. CA-joined plot proved that trichomes could be used as distinguishing characteristic. Therefore, we suggested that the type of indumentum and the most abundant glandular and non-glandular trichomes have high taxonomic value in species identification within the genus.